Capacitor placement and sizing to minimize losses in a radial distribution network considering uncertainty using modified affine arithmetic division. (September 2021) - Adusumilli, Bala Surendra; Raj, Vinod; Adusumilli, Vijaya Bhaskar
Abstract: In a distribution system, load and distributed generation connected to a feeder are subject to uncertainty. Conventional capacitor placement and sizing methods do not consider uncertainty in power injections, due to which the results may be erroneous. In literature, affine arithmetic (AA) is one of the tools used for incorporating uncertainty in power system analysis. However, conventional division operation in AA gives rise to extra noise terms in the resulting affine form, which are not due to the actual uncertainty sources but are due to the nonaffine operations. The present work incorporates modified AA division which does not generate any additional noises, thereby improving the accuracy. Buses in the distribution network are ranked in decreasing order of rate of change of active power loss in line with respect to the change in the effective reactive power flow in that line. The top three ranked buses are chosen as candidate buses for capacitor connection. The required affine reactive current injection at the candidate buses is calculated, and the corresponding affine capacitive kVAR required is obtained through modified AA-based backward/forward sweep (BFS) power flow analysis. The intervals for the cost incurred in losses, voltage profiles with and without capacitor are calculated, and savings for capacitor connected system is calculated. Switchable capacitors are used for reactive power injection. The proposed method is tested on 15, 33 and 118 bus radial distribution systems. The results show that the proposed modified AA method is accurate than existing interval arithmetic-based method.